BELIEFS AND ATTITUDES ON VIOLENCE AGAINST WOMEN IN PARTNER: SOCIO-DEMOGRAPHICS, FAMILIAR AND FORMATIVE DETERMINANTS - Ferrer Pérez, Victoria A.; Bosch Fiol, Esperanza; Ramis Palmer, M. Carmen; Navarro Guzmán, Capilla (Anales de Psicología / Annals of Psychology, 2006)
At present domestic violence is considered a social problem of first magnitude and is analyzed since a perspective multicausal. But, even since this point of view, is considered that in the base of this causal pyramid there would be a sexist conception of the aggressors, narrowly connected with the exacerbation of traditional male model (Corsi, 1995; Heise, 1997). It given this supposed one, to analyze the determinants of these beliefs and attitudes can suppose a prominent contribution to develop programs of early prevention against this form of violence that be more troops.This work analyzes the role of the formative, family, and sociodemographic factors as determinants of beliefs and attitudes sexists and tolerant toward violence against women in a sample of 1395 university students. Results obtained indicate that the factors studied explain a small percentage of these beliefs and attitudes (between 5% and 13% according to the cases). We described and analyze these results and their possible implications in the design of programs and preventive actions.